Hypoglycemia during treatment with the ketogenic diet in a child with refractory epilepsy-results of continuous glucose monitoring - Brožová, Klára; Holubová, Anna; Bořilová, Petra; Brabec, Marek; Kohout, Pavel; Hadač, Jan; Brož, Jan (Neuro endocrinology letters, 2021)
The ketogenic diet (KD) is an effective treatment for intractable epilepsy in children. Hypoglycemia can be one of its side-effects, which is considered to be present mainly during the introductory phase of KD. Continuous glucose monitoring in a 6-year old non-diabetic child treated with KD for more than 8 months revealed long periods of asymptomatic hypoglycemia (8.9% of the total time under 2.5 mmol/l, 10.6% of the total time in the range between 2.5-3.0, 29.1% in the range of 3.0-3.6 mmol/l). The episodes of serious hypoglycemia were associated with a fasting state. The amount of sacharides in KD was increased with substantial glycemic profile improvement.